Ethical Violations Of Constitutional Judges: Study Of The Decision Of The Honour Panel Of The Constitutional Court (MKMK) Number : 2/MKMK/L/11/2023 - Hanifah, Hanifah; Zainuddin, Zainuddin; Maghfira, Saadatul; Efendi, Roni (Institut Agama Islam Negeri Batusangkar, 2024)
This study examines the urgency of a code of ethics for Constitutional Court judges, the dichotomy of ethical considerations in the Honorary Council of the Constitutional Court's (MKMK) Decision Number: 2/MKMK/L/11/2023, and the considerations underlying this decision. Using a normative juridical approach through literature review, the research explores ethical violations by Constitutional Court judges based on sources such as books, journals, and online materials. The findings reveal that the code of ethics plays a crucial role in maintaining judges' independence, integrity, and professionalism. The MKMK decision separates ethical and legal aspects, emphasizing that ethical violations should not be equated with legal violations. In the case of Anwar Usman, a serious ethical breach led to his removal as Chief Justice of the Constitutional Court, although he was not dishonorably discharged as a judge. MKMK's considerations included legal facts, philosophical principles, and social impacts. This decision avoids legal uncertainty by imposing sanctions tailored to ethical, not legal, violations.